Searching online to buy commonly prescribed psychiatric drugs. (February 2018) - Monteith, Scott; Glenn, Tasha
Abstract: The use of online pharmacies to purchase prescription drugs is increasing. The patient experience when searching to buy commonly prescribed psychiatric drugs was investigated. Using the search term "buy [drug name] online" in Google, 38 frequently prescribed drugs, including 13 with a high potential for abuse, were searched by brand and generic names. The first page of results were analyzed, including with pharmacy certification checkers and ICANN WHOIS. Search results for all drugs yielded 167 pharmacies, of which 147 (88%) did not require a prescription. Considering all searches, the average number of pharmacies requiring a prescription was 2.7 for a brand name drug and 2.4 for a generic name. A phrase like "buy without a prescription" usually appeared on the search results page. All results for drugs with a high potential for abuse were for illegal pharmacies. Information from certification agencies was often conflicting. Most pharmacies were registered internationally. Patients searching online to purchase prescription psychiatric drugs are presented predominantly with illegal pharmacies, and find conflicting certification data. Patient education should address typical search results. Societal pressures may increase the use of online pharmacies including prescription drug costs, stigma, loss of trust in expert opinion, and the changing patient role. Highlights: Results from searching online to buy 38 prescription psychiatric drugs were studied. Predominantly illegal pharmacies on the first page of search results. All illegal pharmacies when search for drugs with a high potential for abuse. Pharmacy certification data conflicting. Websites often registered offshore. Patient education should address typical search results.